Mapping the literature of transcultural nursing - Murphy, Sharon C. (Medical Library Association, 2006)
Overview: No bibliometric studies of the literature of the field of transcultural nursing have been published. This paper describes a citation analysis as part of the project undertaken by the Nursing and Allied Health Resources Section of the Medical Library Association to map the literature of nursing. Objective: The purpose of this study was to identify the core literature and determine which databases provided the most complete access to the transcultural nursing literature. Methods: Cited references from essential source journals were analyzed for a three-year period. Eight major databases were compared for indexing coverage of the identified core list of journals. Results: This study identifies 138 core journals. Transcultural nursing relies on journal literature from associated health sciences fields in addition to nursing. Books provide an important format. Nearly all cited references were from the previous 18 years. In comparing indexing coverage among 8 major databases, 3 databases rose to the top. Conclusions: No single database can claim comprehensive indexing coverage for this broad field. It is essential to search multiple databases. Based on this study, PubMed/MEDLINE, Social Sciences Citation Index, and CINAHL provide the best coverage. Collections supporting transcultural nursing require robust access to literature beyond nursing publications.